Right-Side Paratracheal Lymph Node Dissection during Single-Incision Thoracoscopic Surgery Featuring Placement of a Bidirectional Retraction Suture - Park, Jong Myung; Kim, Do Hyung (The Thoracic and Cardiovascular Surgeon, 2017)
In single-incision thoracoscopic surgery (SITS), multiple instruments are inserted through a single working window and at least three hands must move within the limited operative field. When lobectomy is required, SITS has not been preferred for right-side paratracheal lymph node dissection because of instrument collisions. We used our bidirectional traction suture technique to eliminate the need for an azygos vein retractor during dissection, and thereby overcame the instrument collision problem.
Keywords: single-incision thoracoscopic surgery; VATS; lung cancer; node dissection